Diagnostics of parasitic diseases. Myths of the present - S. S. Kozlov; V. S. Turitsin; A. V. Laskin (Журнал инфектологии, 2014)
Diagnostics of parasitic diseases in many medical laboratories is carried out with a bad quality. Principal causes are the low level of qualification of laboratorians and a small amount of laboratory methods which are used. The majority of practising doctors has bad knowledge about diseases. All this serves as base for occurrence in the market of medical services of various pseudoscientific methods of diagnostics of parasitic diseases, such as Voll-method and its analogues, including a method of bioresonant diagnostics, scanning of the crushed drop of blood, including a dark field method, diagnostics on pulse, detection of toxins of parasites in salivaric crystal amilase and others. These methods cannot be scientific to be the methods of demonstrative medicine often lead to development of parasitic phobias of patients.